Sexed pistols the gendered impacts of small arms and light weapons - Farr, Vanessa; Myrttinen, Henri; Schnabel, Albrecht (United Nations University Press, 2009)
Every day, small arms and light weapons (SALW) kill and maim, wound and threaten millions of adults and children, whether combatants and civilians in war zones or gangs and communities in degraded "peacetime" environments that are characterized by large-scale violence. Due to their widespread availability, mobility and ease of use prolific SALW have become central to maintaining social dislocation, destabilization, insecurity and crime in the build-up to war, in wartime and in the aftermath of violent conflict. Small arms are misused within domestic settings, as well as in public spaces, and they affect everyone in the community without regard to sex or age. Although the impacts of these weapons can be vastly different for women and men, girls and boys, a careful consideration of gender and age is rare in the formulation of small arms policy, of planning small arms collection or control, or even in small arms research. To counter the effects of prolific SALW, their role in reinforcing and maintaining gender- and age-specific violence must be more deeply analyzed and the results applied at the policy and operational level. This work should be undertaken in war-afflicted contexts, in societies suffering from elevated levels of social violence and/or severe underdevelopment, and in those tolerant of the presence of individually owned firearms. Contributors to this book draw on experience and research from around the world on the nexus of gender, age, violence and small arms in developing and developed countries. Their findings feed into a number of recommendations for future policy formulation, program implementation and research designed to further illuminate and counteract the firing of the "sexed pistol".--Publisher's description.